Türkiye’s European Union Accession Process Evaluation in The Context of Kemalism - Öcal, Enver Emre (Border Crossing, 2023)
Republic of Türkiye's involvement with European integration dates back to Democrat Party period. It is clear how difficult and questionable this period of many years is. Türkiye 's European Union accession process, which started to accelerate especially since the first half of the 2000s, was resolutely criticized by many nationalist intellectuals in the same period. The central point of these criticisms was that the European Union process would wear out the nation state and was absolutely incompatible with Kemalist principles. In terms of the ideology of Kemalism, which was shaped as the mortar of the nation-building project in the early Republic period, it was undoubtedly an acceptable fact that the European Union membership, which would mean the transfer of the sovereignty of the nation-state, was viewed negatively. Based on the fact in question, the aim of this article is to give a brief summary of the European Union process, which accelerated in the first half of the 2000s and gradually faded in the second half, and then to evaluate the European Union membership process from the Kemalism ideology perspective. Thus, it will be put forward whether the EU membership process and the Kemalism ideology constitute two separate poles, as asserted by nationalist intellectuals.